Swann's Way: Youth, Personal Affinities, and Acculturation Through Sport in Nineteenth Century France - Bourmaud, François (Frontiers in Sports and Active Living, 2021)
This study of two Franco-British cultural mediators and their entourage explores the criteria of age and personal affinities in the process of acculturation through sports in 19th century France. The youth of those who were the first to take up on modern sports is an element that at first seems obvious, but it is probable that up until now this has been underestimated in the understanding of the way individuals opened up to embrace these new activities. Nevertheless, this factor is powerful, in particular when crossed with personal links such as friendship or camaraderie which prompt the sharing and discovery of sporting activities. Despite their dual culture, Alfred Swann (1863-1928) and Cosme de Satgé (1840-1898) did not adopt British pastimes with the same enthusiasm: the former discovered modern sport when he was an adolescent and became an active agent in their spread in Paris whereas the latter did not manage to truly appreciate and pass on British Leisure activities he discovered after he had turned 30. Moreover, both cases underline the fact that sports diffusion often follows the channels of personal affinities: the young lycée pupils around Alfred Swann, like Cosme de Satgé’s children, were acculturated through British sports at the time of their adolescence, not by adults, but by friends and chums of their age.